2004
DOI: 10.1016/j.ejcts.2003.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of blood vessels as significant prognostic factor in radically resected T1-3N0M0 non-small-cell lung cancer

Abstract: In resectable N0 patients with NSCLC the microscopic invasion of blood vessels should be considered as an additional prognostic parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 10 publications
5
59
1
1
Order By: Relevance
“…Furthermore vascular invasion, along with other published studies [25][26][27][28], in our large series resulted as another strong independent prognostic factor. Although prospective studies are needed, our findings underline the importance of a careful evaluation of lymph nodes and vascular invasion in resected NSCLC as it may provide additional useful information for identifying patients who are at high risk and who may be candidates for further medical treatment after or before surgery.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore vascular invasion, along with other published studies [25][26][27][28], in our large series resulted as another strong independent prognostic factor. Although prospective studies are needed, our findings underline the importance of a careful evaluation of lymph nodes and vascular invasion in resected NSCLC as it may provide additional useful information for identifying patients who are at high risk and who may be candidates for further medical treatment after or before surgery.…”
Section: Discussionsupporting
confidence: 78%
“…Naito et al [26] Gabor et al [27] examined 72 patients and reported that vascular invasion at univariate together with multivariate analysis, was a significant prognostic factor in patients with resected, node-negative NSCLC whereas lymph vessel infiltration had no significant impact on outcome. In particular if it was present invasion of the blood vessels the survival rate was 23.5%, in cases without invasion 74.5% (p<or=0.01) [27] (Table 2). In contrast, Fujisawa and colleagues reported both blood (p=0.0046) and lymphatic vessel invasion (p=0.0267) as prognostic factors in 66 NSCLC [13].…”
Section: Introductionmentioning
confidence: 99%
“…patients, including stage I patients, who have undergone radical resection (Ichinose et al, 1994;Kessler et al, 1996;Duarte et al, 1998;Port et al, 2003;Gabor et al, 2004;Sakao et al, 2004); the frequency of radical resection generally ranges from 15 to 36% in the literature (Rigau et al, 2002;Funai et al, 2011). In our research, we retrospectively studied the follow-up records of stage I NSCLC patients to analyze the relationship between LVI and prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…[20][21][22][23] A number of studies [24][25][26] have evaluated the prognostic impact of large-vessel (arterial and/ or venous) invasion independent of lymphatic invasion with somewhat conflicting results. For this reason, it is permissible to report the presence of vascular and/or lymphatic invasion under the single heading of lymphovascular invasion.…”
Section: Microscopic Elementsmentioning
confidence: 99%